Prognostic Significance of Prognostic Nutritional Index in Esophageal Squamous Cell Carcinoma Patients Undergoing Radical Radiotherapy: A Propensity Score Matching Analysis. (3rd July 2022) - Zhao, Yan; Shen, Wenbin; Song, Chunyang; Su, Jingwei; Wu, Peiwen; Wang, Xuan; Yan, Ke; Xu, Jinrui; Zhu, Shuchai
Abstract: Background: The preoperative prognostic nutritional index (PNI) is associated with postoperative complications and long-term survival of various cancers. However, its role in esophageal squamous cell carcinoma (ESCC) is inconclusive. The aim of this study was to identify the prognostic value of PNI in predicting survival in ESCC patients undergoing radical radiotherapy. Methods: We retrospectively reviewed 354 ESCC patients undergoing radical radiotherapy. The time-dependent receiver operating characteristics was used to determine the optimal cutoff value. The association between PNI and survival was determined by Kaplan-Meier method and Cox regression model. Propensity score matching was applied to balance the baseline characteristics. Results: PNI was positively correlated with hemoglobin ( P < 0.001) and prealbumin ( P < 0.001). The optimal cutoff value of PNI was set at 50.5. The 5-year overall survival (OS) in low PNI group and high PNI group were 20.8% and 34.0%, respectively ( P < 0.001). The 5-year progression free survival in patients with low PNI and high PNI were 15.2% and 28.5%, respectively ( P = 0.001). Multivariate analysis showed that PNI was a significant predictor for OS ( P = 0.038). In the PSM analysis, PNI still remained an independent predictor for OS ( P = 0.015). Conclusions: The PNI is a significant and independent predictor for OS of ESCC patients undergoing radical radiotherapy.